2012
DOI: 10.1097/scs.0b013e3182519f24
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Dexmedetomidine in Ischemia-Reperfusion Injury

Abstract: We conclude that administering dexmedetomidine before I/R periods can reduce ischemia-reperfusion injury of flaps, and it has a beneficial effect on flap survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…A decrease in kidney tissue MDA level in the sepsis + dex group suggests that dexmedetomidine attenuates lipid peroxidation. Dexmedetomidine reduced the brain and testis MDA levels in ischemia-perfusion models in previous studies [5255]. However, we did not find any study that investigates the effects of dexmedetomidine on lipid peroxidation in sepsis.…”
Section: Discussionmentioning
confidence: 56%
“…A decrease in kidney tissue MDA level in the sepsis + dex group suggests that dexmedetomidine attenuates lipid peroxidation. Dexmedetomidine reduced the brain and testis MDA levels in ischemia-perfusion models in previous studies [5255]. However, we did not find any study that investigates the effects of dexmedetomidine on lipid peroxidation in sepsis.…”
Section: Discussionmentioning
confidence: 56%
“…In agreement with these results, an investigation conducted by the authors also demonstrated that, prior to and following the ischemic insult, DEX administration, at doses of 10 and 30 µg/kg, reduced tissue MPO activity levels. This reduction was observed at the end of a 12-h and at the end of a seven-day reperfusion (59). However, DEX, at clinically relevant doses, did not significantly affect the expression of inflammatory molecules in activated macrophages.…”
Section: Inflammatory Responsementioning
confidence: 82%
“…An epigastric island skin flap 3 × 6 cm in size was made in the left lower quadrant of the abdomen, leaving the superficial epigastric artery and vein as the only connections, as described by Manson et al The femoral artery and vein were isolated proximally and distally. Ischemia was induced by applying a single microvascular clamp across the pedicle vessels (Figure ), as described by Uysal et al After 6 hours of ischemia, the clamp was removed and the pedicles were examined under an operating microscope to document flap reperfusion, and the flap was sutured to its donor site with a 5‐0 silk continuous suture. Flaps that did not reperfuse were not included.…”
Section: Methodsmentioning
confidence: 99%